(untitled) (Journal of Partial Differential Equations, 2018)
In this article, we apply five different techniques, namely the (G′/G)-expansion method, an auxiliary equation method, the modified simple equation method, the first integral method and the Riccati equation method for constructing many new exact solutions with parameters as well as the bright-dark, singular and other soliton solutions of the (2+1)-dimensional nonlinear cubic-quintic Ginzburg-Landau equation. Comparing the solutions of this nonlinear equation together with each other are presented. Comparing our newresults obtained in this articlewith thewell-known results are given too.